S62 Identifying the child (5–12 years) with asthma at increased risk of attacks: the at-risk child with asthma (arc) systematic review. (15th November 2017) - Buelo, A; Mclean, S; Flores-Kim, J; Julious, S; Shields, M; Paton, J; Henderson, J; Bush, A; Pinnock, H
Abstract : Introduction and Objectives: Asthma is the commonest long-term condition in children with attacks impacting on both school attendance and quality of life. Identifying the child at increased risk of future asthma attacks could inform clinical management and targeting of care. We aimed to systematically review the literature to identify and weight factors associated with increased risk of attacks in children with asthma aged 5–12 years. Methods: Using Cochrane methodology, we systematically searched six databases and undertook forward and backward citation searches, with no date/language restrictions. Two reviewers independently selected studies for inclusion, assessed methodological quality, and extracted data. An expert panel of four clinicians independently assessed each factor for both magnitude of risk and degree of confidence in that assessment, based on study quality, effect sizes, biological plausibility, and consistency of Results Consensus was achieved by discussion and agreed at a multidisciplinary workshop. Results: From 16 109 records, we included 69 papers (29 cohort, 4 case-control, 36 cross-sectional studies) providing data on 32 potential factors associated with an increased risk of asthma attacks. The panel had high confidence that previous asthma attacks were associated with greatly increased risk of future attacks. Poor access to care and persistent symptoms were associated with moderately/greatly increased risk. A moderately increased risk of attack was associated with sub-optimal drug regimen (low controller/total therapy ratio), comorbid atopic/allergic disease, African-American ethnicity (US studies), poverty, and vitamin D deficiency. Environmental tobacco smoke (ETS) exposure, younger age, and obesity were associated with slightly increased risk. Gender, urban residence, and Hispanic ethnicity (US studies) were not associated with risk. The evidence for other factors was inconclusive. Conclusions: Assessment of clinical and demographic features (especially persistent symptoms, previous attacks, and sub-optimal drug regimen) may help clinicians to 'spot the child' at increased risk of asthma attacks and focus appropriate management. Population level factors (poverty, poor access to care) may be used by health service planners and policymakers to target healthcare initiatives.